Parental origin and mechanisms of formation of cytogenetically recognisable de novo direct and inverted duplications. Issue 4 (1st April 2000) - Kotzot, Dieter; Martinez, Maria-Jose; Bagci, Gulseren; Basaran, Seher; Baumer, Alessandra; Binkert, Franz; Brecevic, Lucrecja; Castellan, Claudio; Chrzanowska, Krystyna; Dutly, Fabrizio; Gutkowska, Anna; Karaüzüm, Sibel Berker; et al.
Abstract : Cytogenetic, FISH, and molecular results of 20 cases with de novo tandem duplications of 18 different autosomal chromosome segments are reported. There were 12 cases with direct duplications, three cases with inverted duplications, and five in whom determination of direction was not possible. In seven cases a rearrangement between non-sister chromatids (N-SCR) was found, whereas in the remaining 13 cases sister chromatids (SCR) were involved. Paternal and maternal origin (7:7) was found almost equally in cases with SCR (3:4) and N-SCR (4:3). In the cases with proven inversion, there was maternal and paternal origin in one case each. Twenty three out of 43 cytogenetically determined breakpoints correlated with common or rare fragile sites. In five cases, including all those with proven inverse orientation, all breakpoints corresponded to common or rare fragile sites. In at least two cases, one with an interstitial duplication (dup(19)(q11q13)) and one with a terminal duplication (dup(8) (p10p23)), concomitant deletions (del(8) (p23p23.3) and del(19)(q13q13)) were found.